Visual Short-Term Memory Load Reduces Retinotopic Cortex Response to Contrast - Konstantinou, Nikos; Bahrami, Bahador; Rees, Geraint; Lavie, Nilli (My University, 2012)
Load Theory of attention suggests that high perceptual load in a task leads to reduced sensory visual cortex response to task-unrelated stimuli resulting in "load-induced blindness" [e.g., Lavie, N. Attention, distraction and cognitive control under load. Current Directions in Psychological Science, 19, 143-148, 2010; Lavie, N. Distracted and confused?: Selective attention under load. Trends in Cognitive Sciences, 9, 75-82, 2005]. Consideration of the findings that visual STM (VSTM) involves sensory recruitment [e.g., Pasternak, T., & Greenlee, M. Working memory in primate sensory systems. Nature Reviews Neuroscience, 6, 97-107, 2005] within Load Theory led us to a new hypothesis regarding the effects of VSTM load on visual processing. If VSTM load draws on sensory visual capacity, then similar to perceptual load, high VSTM load should also reduce visual cortex response to incoming stimuli leading to a failure to detect them. We tested this hypothesis with fMRI and behavioral measures of visual detection sensitivity. Participants detected the presence of a contrast increment during the maintenance delay in a VSTM task requiring maintenance of color and position. Increased VSTM load (manipulated by increased set size) led to reduced retinotopic visual cortex (V1-V3) responses to contrast as well as reduced detection sensitivity, as we predicted. Additional visual detection experiments established a clear tradeoff between the amount of information maintained in VSTM and detection sensitivity, while ruling out alternative accounts for the effects of VSTM load in terms of differential spatial allocation strategies or task difficulty. These findings extend Load Theory to demonstrate a new form of competitive interactions between early visual cortex processing and visual representations held in memory under load and provide a novel line of support for the sensory recruitment hypothesis of VSTM.
Keywords: Contrast sensitivity; Controlled clinical trial